Turning Trash into Treasure: The Use of Vulcanized Ash Filters and Glass Waste for Renewable Energy - Kusnere Zane; Rupeika Diana; Spalvins Kriss; Mika Taras (Environmental and Climate Technologies, 2023)
Biomethanation is a prospective method to integrate a renewable solar or wind power grid with a biogas grid, where excess energy can be used to produce hydrogen for the biomethanation of the biogas to produce biomethane. The use of biotrickling filter reactors with appropriate carrier materials for biomethanation is essential for the immobilisation of hydrogenotrophic methanogens on the surface of the packing material. This study tested the suitability of filter materials made from woodchip ash (FA and CA) and glass waste (GF) for methanogenesis in biotrickling filter reactors using comparative performance analysis. The readily available and widely used expanded clay pallets (EC) and polyurethane foam (PUF) in biomethanation were used for comparison. The manometric method and BMP test are used to determine the rate of CH4 production. CH4 produced using filter materials decreases in the order GF>EC >PUF>FA>CA, respectively. The physical parameters of tested materials are compared to other filter materials commonly used in biomethanation applications. Glass foam (GF) that is made from glass waste showed the best biomethane production rate of 201.2 NmL/Lmaterial, as it has the best physical properties for methanogenesis in biotrickling filter reactors such as low volume density, high external porosity, and neutral pH. Ash waste recycling is related to its specific chemical properties, as it is alkaline and contains heavy metals that can leach out and negatively affect living organisms.